Migration is context for understanding the lifestyle: an anthropological study in the city of Ouargla - Boudemagh, Khaoula; Aouaidjia, Samah (Journal of Human Sciences, 2023)
The phenomenon of migration from an anthropological perspective expresses the set of methods, strategies and practices employed by the immigrant to achieve integration into the local society, and thus results in the formation of a special way of living that contributes to bringing about social-cultural change, thus emphasizing the inevitability of dynamism as opposed to the static stability and stability. Through this article, we will try to shed light on the contribution of migration to understanding the way of life.